EFFECTIVENESS OF QUIZ TEAM AND MURDER METHOD ON LEARNING ACTIVITIES AND PROBLEM SOLVING SKILLS IN SOCIAL SCIENCE LEARNING FOR 8th GRADE STUDENTS AT UPI LABORATORY JUNIOR HIGH SCHOOL - Darwanti, Darwanti (JURNAL PENDIDIKAN ILMU SOSIAL, 2017)
There are three objectives that shape the study, first, the study is aimed at identifying different problem-solving skills of the students' who were acquainted with quiz team, lecture and MURDER method. Secondly, the study is to point out the difference of students' problem-solving skills when they are exposed to the three methods in a high, moderate, and low intensity. The third objective is to determine interactions among learning methods, learning activities and problem-solving skills. Quasi experiment is used as a method of the study by applying two experiment classes, and one controlled factorial designed class. In analyzing the data, a two-way Anova analysis and variants analysis are implemented to measure the interaction level among the three variables. The results of the study indicate that (1) there are differences in students' problem-solving skills who were exposed to quiz team, lecture and MURDER method; (2) there are also differences in students' problem-solving skills when they were exposed by the mentioned methods in a high, moderate, and low intensity; there are no relevant interactions among learning methods, learning activities and problem-solving skills. The current results are presented such that they can be used as an aid to the methods of social science learning.Â